" التنظيم القانوني لعقد السلم وتطبيقه العملي" - غالــــــم ياســـر (Tobruk University Journal of Social and Human Sciences, 2023)
Contract Assalam is considered possibility to be one of the most important and the most important forms of financing and investment in participatory banks or even at the state level, especially as it enjoys applicability in the various agricultural, industrial and commercial sectors. The widespread use of this funding formula in Moroccan participatory banks is limited by the high risks associated with this contract, which prompted us to search for preventive methods and techniques to manage and reduce these risks, especially with regard to a large download by the Takaful Insurance Institution to cover the risks of financing by Salam.